Clinical and radiological features of incarcerated hernia - Ahmad, Doha J.; Alqhtani, Ali J.; Alzunidi, Mashel A.; Alowayyid, Jawaher A.; Almindil, Fatima K.; Azeb, Khaled A.; Alabbad, Naif A. A.; Hassani, Mousa A.; Alruwaili, Omar M.; Alelyani, Salem F.; Alalkami, Mohammed Y. (International Journal Of Community Medicine And Public Health, 2022)
Many complications were reported secondary to herniation, including strangulation and incarceration, leading to intestinal obstruction and related clinical manifestations. Treating such cases is largely dependent on appropriately diagnosing and evaluating them to enhance the prognosis and prevent a recurrence. In the present literature review, we have discussed incarcerated hernias’ clinical and radiological features. Physical examination is very important in establishing the diagnosis of these events and obtaining a thorough history from the patient. Most patients present with abdominal pain, tenderness, and erythematous changes. Signs of intestinal obstruction might also be reported when this complication develops. Signs include acute abdominal pain, nausea, and vomiting. Radiological findings might show the presence of air to fluid appearance. Clinicians should be aware of these clinical manifestations and perform an adequate physical examination to establish a proper diagnosis and manage these cases. The process of decision-making is important before deciding the most appropriate management approach. Therefore, it is important to assess patients before moving to the next steps.